Agroforestry for Soil Quality Maintenance, Climate Change Mitigation and Ecosystem Services - Rao, A. Subba; Saha, R. (Indian Farming, 2015)
Agroforestry not only has positive impact on biodiversity but it also promotes the use of biomass fuels, replacing the fossil fuels, thereby contributing to net reduction in CO2 emissions. It provides the best example of promoting mitigation and adaptation synergy in addressing climate change. Also, an integrated farming approach would bring about change in soil quality, ground water level and thereby improving agricultural productivity, giving the farmer a diversity of products. Planting of multipurpose tree species in non-forest land categories serves a dual purpose, i.e. promotion of biodiversity and carbon sequestration. Tree also provides economic rewards from the non carbon benefits. Besides the potential of agroforestry system to accumulate and sequester carbon, these systems could evolve into a technological option for reducing the vulnerability of farming system to climate variability and climate change impacts and for obtaining ecosystem services like clean air and water.